Genome scale modeling of yeast metabolic pathways - Harmesh Singh Dhillon. (2011)
The field of metabolic engineering is one that has been experiencing extraordinary growth in the past few years due to its adoption in a number of industrial biotechnological processes. Biofuel production is one such process and is rapidly catching the world’s attention due to its potential use as an alternative form of energy. The aim of this project is to firstly, study the metabolic pathways in the eukaryote Saccharomyces cerevisiae. With this analysis serving as a foundation, we hope to devise novel methods of in silico metabolic engineering via the use of the BioMet Toolbox in order to increase productivity and yield ratios of fatty acids that can be utilized for biofuel production. Focusing particularly on NADPH production, we identified 8 related genes (ZWF1, GND2, GND1, IDH1, TDH1, TDH2, TDH3 and MAE1) and proceeded to run each through a series of wild type, single gene deletion and flux overexpression simulations on the BioOpt software within the BioMet Toolbox. Of the results obtained, several trends between the selected genes and growth or fatty acid biosynthesis were identified. For example, ZWF1 flux increased with growth overexpression and remains unchanged with fatty acid biosynthesis overexpression. In addition to this, ZWF1 and GND1 follow a relationship described by flux ZWF1  flux GND1. TDH2 flux also showed a surprisingly high flux with respect to growth overexpression.